Study on construction of comprehensive community health databases through linkage between Community Health Survey data and other community contextual indicators in Korea - Kim, Dong-Hyun (International Journal of Population Data Science, 2018)
Introduction Since 2008, Korea Centers for Disease Control and Prevention have performed nationwide survey, Korea Community Health Survey(K-CHS) annually, to collect information on pervalences of smoking, drinking, physical activity, obesity, diet, oral health, and other health-related activities among randomly selected community-dwelling residents aged 19 years or over in 250 administrative districts(Si-gun-gu). Objectives and Approach This study aims to build comprehensive data library through leakage of area-based data collected from K-CHS and other community contextual health indicators from various government databases. For this purpose, we reviewed other databanks on community status health indicators comprehensively and tried to search linkage information from the related national public database. Results We reviewed the community health model, which is theoretically and empirically proven in other studies and tried to propose health determinants of community health through population health perspectives. We collected information on health outcomes of each community, measured by overall mortality and self-rated health. We also assessed health determinants, measured in five domains including social network, health behaviors, clinical care, social and economic factors, and physical environment. Childhood environment was dealt briefly. Geo-coded data on selected core indicators were collected for each domain and the validity, reliability, sensitivity, and robustness of these measures was evaluated. We constructed comprehensive databases through linkage of health outcomes and health determinants. We also suggested summary sheet template, comprizing comprehensive community health status indicators. Conclusion/Implications In conclusion, we anticipate evidence-based community health intervention and evaluation of its performance through utilizing comprehensive databases on community health.